A green wave band based method for urban arterial signal control - Bao-Lin Ye; Weimin Wu; Xuanhao Zhou; Weijie Mao; Yi-Sheng Huang (Proceedings of the 11th IEEE International Conference on Networking, Sensing and Control, 2014)
Optimal signal timing is an efficient and effective method to mitigate traffic congestion in urban road traffic networks. In this paper, we propose a new method for signal-timing optimization of urban arterial roads. The main idea to the method is to design a bi-direction green wave band for arterial roads. In order to reduce delay and stops, an arterial road signal coordination approach is developed. In addition, the arterial signal coordination approach has been expanded to deal with the problem of coordination for urban traffic networks coordination control. Finally, simulation experiments are given to illustrate the effectiveness of the proposed method.